Assembly of the phagocyte NADPH oxidase: binding of Src homology 3 domains to proline-rich targets. - Leto, T L (1994)
The NADPH oxidase responsible for generation of superoxide anion and related microbicidal oxidants by phagocytes is assembled from at least five distinct proteins. Two are cytosolic components (p47-phox and p67-phox) that contain Src homology 3 (SH3) domains and associate with a transmembrane cytochrome b558 upon activation. We show here that the SH3 domains of p47-phox bind to proline-rich sequences in p47-phox itself and the p22-phox subunit of cytochrome b558. Binding of the p47-phox SH3 domains to p22-phox was abolished by a mutation in one proline-rich sequence (Pro156-->Gln) noted in a distinct form of chronic granulomatous disease and was inhibited by a short proline-rich synthetic peptide corresponding to residues 149-162 of p22-phox. Expression of mutated p22-phox did not restore oxidase activity to p22-phox-deficient B cells and did not enable p22-phox-dependent translocation of p47-phox to membranes in phorbol ester-stimulated cells. We also show that the cytosolic oxidase components associate with one another through the C-terminal SH3 domain of p67-phox and a proline-rich C-terminal sequence in p47-phox. These SH3 target sites conform to consensus features deduced from SH3 binding sites in other systems. We propose a model in which the oxidase complex assembles through a mechanism involving SH3 domains of both cytosolic proteins and cognate proline-rich targets in other oxidase components.